An H I interstellar bubble surrounding WR 85 and RCW 118 - Vasquez, Javier (2005)
We analyse the distribution of the interstellar matter in the environs of the Wolf-Rayet star LSS 3982 (= WR 85, WN6+OB?) linked to the optical ring nebula RCW118. Our study is based on neutral hydrogen 21-cm line data belonging to the Southern Galactic Plane Survey (SGPS). The analysis of the H I data allowed the identification of a neutral hydrogen interstellar bubble related to WR85 and the 25-arcmin-diameter ring nebula RCW 118. The H I bubble was detected at a systemic velocity of -21.5 km s-1, corresponding to a kinematical distance of 2.8 ± 1.1 kpc, compatible with the stellar distance. The neutral structure is about 25 arcmin in radius or 21 ± 8 pc, and is expanding at 9 ± 2 km s-1. The associated ionized and neutral masses amount to 3000 M⊙ . The carbon monoxide (CO) emission distribution depicts a region lacking CO coincident in position and velocity with the H I structure. The 9.3-arcmin-diameter inner optical nebula appears to be related to the approaching part of the neutral atomic shell. The H I void and shell are the neutral gas counterparts of the optical bubble and have very probably originated in the action of the strong stellar wind of the central star during the O-type and WR phases on the surrounding interstellar medium. The H I bubble appears to be in the momentum conserving stage.